Выбор меры различия значений образцового и отфильтрованного биомедицинских сигналов - Сергеев-Горчинский, Алексей Александрович (НТУ "ХПИ", 2017)
В статье рассмотрен выбор меры различия результатов фильтрации искажённых электрических биомедицинских сигналов в задаче поиска оптимальных значений параметра цифрового фильтра нижних частот "простое скользящее среднее". Для сравнения были выбраны меры различия – среднеквадратичная ошибка, корень среднеквадратичной ошибки, средняя абсолютная ошибка. Выполнена серия экспериментов по генерированию и фильтрации искажённых сигналов. В результате сравнения выбрана мера, для которой характерно большее количество найденных локальных оптимальных значений параметра цифрового фильтра при высоких уровнях флуктуационной помехи.

The article covers selection of a error measure for the results of filtering distorted quantized periodic signals when searching for optimum values of low band digital filter parameter represented by a "simple moving average" in a non-recursive form. The following error measures were selected for comparison – Mean Squared Error, Root Mean Squared Error, Mean Absolute Error. To perform the experiments, a program library was created for generation of periodic discrete quantized signals, and for their distortion using fluctuating interference (noise) with normal distribution, and for further filtering of the distorted signals. A series of experiments was carried out for the generation and filtering of distorted periodic signals with different noise levels. As a result, error measures were found for filtered signals with different values of the digital filter parameter. Ultimately, a measure was selected based on comparison results, representing greater number of local optimum values of the digital filter parameter at high fluctuating noise levels.
Selection of error measure for reference and filtered biomedical signals values
Keywords: дискретный сигнал; цифровой фильтр; скользящее среднее; оптимальный параметр; discrete signal; digital filter; optimal parameter